TREATMENT OF VIBRIOSIS DISEASE (Vibrio harveyi) IN VANAME SHRIMP (Litopenaeus vannamei, Boone 1931) USING Avicennia alba LEAVES EXTRACT - Dian Rusadi; Wardiyanto Wardiyanto; Rara Diantari (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Avicennia alba is a mangrove plant that often ued by coastal society as a traditional medecine, it is potential to be dveloped as the sources of pharmaceutical. The aim of the research is to examine the effect of Avicennia alba leaves extract various concentrations to Vibrio harveyi infection on vaname shrimp. The addition of the extract is thought to be used as an antibacterial so that it can give effect to the attack of V. harveyi in vaname shrimp. Vaname shrimps (total of 120 shrimps) with a weight of 10±2g/ind were injected intramuscularly with V. harveyi bacteria in 107 CFU/ml density. After the occurrences of clinical symptoms, the shrimps were immersed into A. alba leaves extract with concentration 0 ppm, 150 ppm, 250 ppm, and 350 ppm for 21 days. The results showed that the addition leaves extract can increase shrimp’s survival rate as much as 46.67% and increase the shrimp’s ability to prevent (RPS) V. harveyi infection untill of 70±15%. The mean time of death (MTD) was 106±18.33 hours, it caused there ar active compounds contained such as saponin, tannin, and steroid be suspected antibacterial so that they can protect shrimp from the effect of Vibrio infection damage. Giving a concentration of 250 ppm Avicennia alba leaves extract can treat vaname shrimp which was attacked by V. harveyi better than other treatments.